PENGARUH LATIHAN INTERVAL TRAINING ISTIRAHAT AKTIF TERHADAP PENINGKATAN DAYA TAHAN AEROBIK (VO2MAX) SISWA SSB OGAN ILIR - Lanos, Muhsana El Cintami (Jurnal Olahraga, 2018)
The This research is motivated by the lack of physical training in Ogan Ilir SSB due to inadequate training facilities and infrastructure so that an easy form of training is needed but the benefits are great. The problem in this study is is there any effect of active rest interval training exercises on increasing aerobic endurance (VO2max) of SSB Ogan Ilir students. This study aims to determine whether there is an effect of active rest interval training exercises on increasing aerobic endurance (VO2max) of SSB Ogan Ilir students. The research variable consisted of independent variables, namely active interval training interval training and the dependent variable, namely increased aerobic endurance (VO2max), obtained from a 2.4 Km run test. The study population numbered 32 people. Sampling using the ordinal pairing system with a given initial test (pretest), then the results of the pretest were ranked and divided into two groups namely 16 people for the experimental class and 16 people for the control class. The research method uses quasi-experimental methods. The data collection technique is running 2.4 Km. After that the data is analyzed using the "t" test. The results showed that tcount> t table or t count = 2.89> t table (0.95) = 1.70 with a significant level of 5% (0.05) with dk = 30. The average pre-test for the experimental group was 13, 22 and after receiving treatment the average post-test for the experimental group became 13.06 or increased by 0.57%. Thus, the research hypothesis which states that: "There is an effect of active resting interval training exercises on increasing aerobic endurance (VO2max) of Ogan Ilir SSB students", is acceptable.